Systematic review and meta-analysis of factors that help or hinder treatment decision-making capacity in psychosis. (October 2017) - Larkin, Amanda; Hutton, Paul
Abstract : Background: The evidence on factors that may influence treatment decisional capacity ('capacity') in psychosis has yet to be comprehensively synthesised, which limits the development of effective strategies to improve or support it. Aims: To determine the direction, magnitude and reliability of the relationship between capacity in psychosis and a range of clinical, demographic and treatment-related factors, thus providing a thorough synthesis of current knowledge. Method: We conducted a systematic review, meta-analytical and narrative synthesis of factors that help or hinder treatment decision-making capacity in psychosis, assessing the direction, magnitude, significance and reliability of reported associations. Results: We identified 23 relevant studies ( n = 1823). Psychotic symptoms had small, moderate and strong associations with appreciation, understanding and reasoning respectively. Both verbal cognitive functioning and duration of education had small to moderate correlations with understanding and reasoning. Better capacity was also associated with better insight, better metacognitive ability, higher anxiety and lower perceived coercion. No linear relationship with depression was observed. Interventions linked to improved capacity over time were in-patient care, information simplification, shared decision-making and metacognitive training. Conclusions: Although much is known about the role of symptoms and other clinical variables, effective and acceptable psychological interventions to support capacity in this group are lacking.